2017
DOI: 10.2174/1874325001711010909
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Anterior Shoulder Instability

Abstract: Background:The shoulder is the most complex joint in the body. The large freedom of motion in this joint is the main cause of instability. Instability varies in its degree, direction, etiology and volition and there is a large spectrum of conditions. Methods:Based on literature research and also in our own experience, we propose to elucidate the reader about the natural history of instability and its importance for the appropriate management of this pathology, by answering the following questions:What happens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Arthroscopic Bankart repair is a less invasive procedure with lower complication rates than open bone transfer surgery. 2,7,20,22 There are important patient-specific factors that are evaluated by the surgeon that help to determine the initial recommendation for arthroscopic Bankart repair, open Bankart repair, or the Latarjet procedure to address anterior shoulder instability. In our study, we found a complication rate of 16.7% in the primary Latarjet group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthroscopic Bankart repair is a less invasive procedure with lower complication rates than open bone transfer surgery. 2,7,20,22 There are important patient-specific factors that are evaluated by the surgeon that help to determine the initial recommendation for arthroscopic Bankart repair, open Bankart repair, or the Latarjet procedure to address anterior shoulder instability. In our study, we found a complication rate of 16.7% in the primary Latarjet group.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior shoulder dislocations occur in approximately 2% of the population, with 80% of these occurring in young patients. 26 Recurrent instability and functional shoulder impairment have been shown to develop in up to 92% of these adolescent patients, 7,22,30,33 with young male athletes being at the highest risk for recurrence. 2,24,30 Aside from acute pain, functional impairment, and instability, these patients are now at an increased risk for developing long-term degenerative arthritis, which is correlated with the number of recurrent episodes of dislocation.…”
mentioning
confidence: 99%
“…The general consensus in the literature is that young males who are involved in contact sports are at significantly higher risk for recurrent instability than the general population. 11,44) There may be an interaction between sex and other risk factors, such as age or mechanism of injury. For example, young males may be more likely to sustain an instability event during contact sports.…”
Section: Natural History/risk Factors For Recurrencementioning
confidence: 99%
“…However, some studies have reported that younger patients who are involved in contact or collision sports, or those who require occupationally require the overhead use of the arm, are more likely to have re-dislocation of the shoulder than their less active counterparts or older persons. 11,44) Sachs et al 50) recommended immediate surgical stabilization in young males who practice contact sports with persistent pain or instability, despite a period of initial conservative treatment in the first-time dislocation.…”
Section: Conservative Versus Surgical Treatmentmentioning
confidence: 99%
“…The second part is focused in anterior instability with four reviews of the natural history [ 9 ], management alternatives of bone defects [ 10 , 11 ] and soft tissues [ 12 ] in instability and a fifth over the failed shoulder instability patient [ 13 ]. Three “controversies” papers focus in specially disputed topics: management of the first shoulder dislocation [ 14 ], open or arthroscopic procedures [ 15 ] and associated procedures during Bankart repair [ 16 ].…”
mentioning
confidence: 99%